2013
DOI: 10.1097/fpc.0b013e3283642fb3
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and systematic review of the effect of the donor and recipient CYP3A5 6986A>G genotype on tacrolimus dose requirements in liver transplantation

Abstract: The presence of the CYP3A5 6986A>G polymorphism in the donor affects tacrolimus pharmacokinetics in the recipient, although only the evidence available for the first month after transplantation was of adequate quality for demonstrating a significant difference. The evidence provided here shows no effect of the recipient genotype; however, the quality of the evidence was low, thereby precluding the drawing of firm conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
2
18
2
1
Order By: Relevance
“…In multivariate analysis, besides Donor IL-18 rs5744247 polymorphism as a new biomarker of tacrolimus elimination Research Article the obvious factor daily dose total bilirubin together with donor CYP3A5 and IL-18 gene polymorphisms were identified as independent influence factor of tacroliums C/D ratio. A Previous meta-analysis has shown that it was the donor, rather than recipient CYP3A5 genotype, which is important for tacrolimus pharmacogenetics [40]. Our result that total bilirubin affected tacrolimus clearance was consistent with previous studies that the pharmaco kinetics of tacrolimus was influenced by the total bilirubin level (TBIL) and total plasma proteins [15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…In multivariate analysis, besides Donor IL-18 rs5744247 polymorphism as a new biomarker of tacrolimus elimination Research Article the obvious factor daily dose total bilirubin together with donor CYP3A5 and IL-18 gene polymorphisms were identified as independent influence factor of tacroliums C/D ratio. A Previous meta-analysis has shown that it was the donor, rather than recipient CYP3A5 genotype, which is important for tacrolimus pharmacogenetics [40]. Our result that total bilirubin affected tacrolimus clearance was consistent with previous studies that the pharmaco kinetics of tacrolimus was influenced by the total bilirubin level (TBIL) and total plasma proteins [15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…11,12) However, a recent meta-analysis and systematic review has shown that donor, but not recipient, CYP3A5 polymorphisms were associated with variability in tacrolimus pharmacokinetics in liver transplant patients. 22) The current study confirmed that donor and recipient CYP3A5 rs776746 allele A was associated with lower log-transformed tacrolimus C/D ratios compared to allele G. In the final multiple linear regression model, donor rs776746 polymorphisms contributed to the variation of log-transformed tacrolimus C/D ratios more than that of recipients. We speculate that both donor and recipient CYP3A5 rs776746 polymorphisms are important in tacrolimus pharmacokinetics although donor CYP3A5 polymorphisms are more significant, and this is consistent with a previous report.…”
Section: Discussionsupporting
confidence: 75%
“…4) The phenomenon may be due to the ethnic difference in the allele frequency of rs776746 allele G between Asian populations (63.4-77.0%) and White populations (80.0-93.8%). 22) Prospective, randomized studies have shown that CYP3A5 polymorphism-guided dosing helped to determine appropriate doses of tacrolimus in kidney transplant patients. 23,24) CYP3A5 polymorphism-guided dosing is a step toward translation into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…42 However, we did not observe an effect of CYP3A genotype on rates of acute or chronic rejection. 42 However, we did not observe an effect of CYP3A genotype on rates of acute or chronic rejection.…”
Section: Ta B L E 3 Acute and Chronic Kidney Injurycontrasting
confidence: 66%